Imatinib resistance and blast transformation of chronic myeloid leukemia associated with a novel tri-nucleotide insertion mutation of BCR-ABL kinase domain at position K294 - Nadarajan, V.S.; Ang, C.H.; Syed-Sultan, M.K.; Bee, P.C. (Springer Verlag (Germany), 2012)
A letter to the editor is presented which discusses the introduction of imatinib mesylate (IM) in the medical case of an 18-year old man with in-frame mutations and blast transformation of chronic myeloid leukemia (CML).